Premature ovarian insufficiency in patients with galactosemia - Irina V. Karachentsova; Elena V. Sibirskaya; Adelina A. Khairullina (Педиатрическая фармакология, 2024)
Background. Galactosemia is a congenital disorder of carbohydrate metabolism caused by a defect in any of the enzymes of galactose metabolism. One of the long-term complications is premature ovarian insufficiency (POI), which is more common in patients with the c.563A>G (Q188R) mutation in the homozygous state in the galactose-1-phosphate uridylyltransferase (GALT) gene. At the same time, fertility factors may be higher in patients with POI caused by classical galactosemia (CG) compared with other causes of POI, which makes it difficult to resolve the issue of the need to use fertility preservation methods for this group of patients in the prepubescent period. Case report. This article describes two clinical observations of patients with CG who were diagnosed with hypergonadotropic hypogonadism. Patient A. was initiated hormone replacement therapy (HRT) at the age of 11, and according to the results of osteodensitometry, there is currently no decrease in bone mineral density. In patient C. at the age of 14, before the start of HRT, ovaries without pronounced follicular apparatus, osteopenia and osteoporosis were detected. The issue of the necessity and timing of the use of fertility preservation methods is being considered. Conclusion. Patients with CG are recommended to monitor hormonal profile indicators for timely administration of HRT. Cryopreservation of ovarian tissue should be considered as one of the options for maintaining fertility in patients with CG, taking into account that some of them still have the possibility of spontaneous pregnancy, despite the POI.